The Influence of Socioeconomic Characteristics on Anthropometry, Nutrition Knowledge, and Attitude of People Living With HIV/AIDS Attending Special Treatment Center (STC) National Hospital Abuja, Nigeria - Okorie, Ijioma; Okorie, Adaeze Christiana (Frontiers in Nutrition, 2022)
The work is on influence of socioeconomic status of people living with HIV/AIDS (PLWHA) on their anthropometry, nutrition knowledge and attitude, attending special treatment center (STC) in National Hospital Abuja, Nigeria. A cross sectional study design was carried out in the STC and a total of two hundred and seventy (270 [150 males and 120 females]) PLWHA were used for the study. The PLWHA attend STC once in 2months and subjects were grouped into 16 giving 4 groups per week since the centre runs Monday through Thursday weekly and by 2months, there were altogether 32groups. Socioeconomic characteristics, nutrition knowledge and attitude, and anthropometric data were collected. Data were analyzed using descriptive statistics, Chi-square and regression analysis. The study revealed that 41.1% of PLWHA had poor knowledge of nutrition, 29.1% had both fair and good knowledge while 0.7% had an excellent knowledge. 52.8% had a positive attitude of nutrition. The skinfold status of the respondents showed that 56.0% were malnourished, while their body mass index (BMI) revealed that 49.3% were normal. Gender (being female) and age (being young) had a significant (P < 0.01) influence on the BMI of PLWHA, while being female significantly influenced their skinfold status. Self-employed and being female were strongest (P < 0.01) positive predictors of nutrition knowledge, while low education had a negative influence on their attitude towards nutrition. Good nutrition knowledge, attitude and improved socioeconomic characteristics are important tools in the care process of PLWHA, for sustainable healthy PLWHA, leading to healthy society at large.